2020
DOI: 10.1080/10986065.2020.1765078
|View full text |Cite
|
Sign up to set email alerts
|

Promoting insight into algebraic formulas through graphing by hand

Abstract: Student insight into algebraic formulas, including the ability to identify the structure of a formula and its components and to reason with and about formulas, is an issue in mathematics education. In this study, we investigated how 16-and 17-year-old pre-university students' insight into algebraic formulas can be promoted through graphing formulas by hand. In an intervention of five 90-min lessons, 21 grade 11 students were taught to graph formulas by hand. The intervention's design was based on experts' stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In discussing the findings, we note that the results of this study seem to confirm earlier research about the problems Dutch students have with algebra: students have problems graphing formulas by hand (Kop et al, 2020) and with identifying and using the structure of algebraic expressions (Van Stiphout, Drijvers, & Gravemeijer, 2013). Regular teaching of algebra does not seem to develop these aspects of symbol sense.…”
Section: Limitationssupporting
confidence: 86%
See 2 more Smart Citations
“…In discussing the findings, we note that the results of this study seem to confirm earlier research about the problems Dutch students have with algebra: students have problems graphing formulas by hand (Kop et al, 2020) and with identifying and using the structure of algebraic expressions (Van Stiphout, Drijvers, & Gravemeijer, 2013). Regular teaching of algebra does not seem to develop these aspects of symbol sense.…”
Section: Limitationssupporting
confidence: 86%
“…This suggests that teaching symbol sense in the domain of graphing formulas by hand might be an effective means to teach essential aspects of symbol sense involved in solving non-routine algebra tasks. In a previous study, we showed how to teach graphing formulas by hand, using these essential aspects of symbol sense (Kop et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with other studies [13,27,28], the difficulties include drawing absolute value function graphs without using graphing software and determining x values intervals from the graphs that are satisfying the absolute value inequalities. The difficulties dealing with absolute value function graphs show a lack of symbol sense, i.e., a lack of ability in recognizing function families and graph features from the structure of functions [22,29]. In other studies [30,31], the ability to switch from symbolic algebra to geometrical ideas, showing versatile thinking of different representations, which also shows symbol sense behavior, concerns the ability to intertwine between mathematical topics.…”
Section: Discussion On Absolute Value Inequalitiesmentioning
confidence: 99%
“…Although school textbooks aim to pay attention to mathematical thinking, there is not much explicit instruction on symbol sense. In order to systematically teach symbol sense, Kop (2020) and Kop et al (2021) have suggested teaching students in grades 11 and 12 to graph formulas based on recognition and reasoning.…”
Section: History: Math Curricula In the Netherlands 1998-2021mentioning
confidence: 99%